A metagenomics survey of viral diversity in mosquito vectors allows the first detection of Sindbis virus in Burkina Faso - (:unkn) unknown (My University, 2025)
Arboviruses (i.e., Arthropod-borne viruses) pose a threat to human health worldwide. This taxonomically-diverse group includes numerous viruses that recurrently spread into new regions. Therefore, periodic surveys of the arboviral diversity in a given region can help optimize the diagnosis of arboviral infections. However, such surveys are infrequent, especially in low-income countries. Consequently, case investigation is often limited to a fraction of the arboviral diversity. This situation is likely to result in undiagnosed cases. Here, we investigated the diversity of mosquito-borne arboviruses in two regions of Burkina Faso. To this end, we used untargeted metagenomics to screen mosquitoes collected over three years in six urban and rural areas. The analysis focused on two mosquito species, Aedes aegypti and Culex quinquefasciatus, considered to be among the most important vectors of arboviruses worldwide. The screening detected Sindbis virus (SINV, Togaviridae) for the first time in Burkina Faso. This zoonotic arbovirus has spread from Africa to Europe. SINV causes periodic outbreaks in Europe but its distribution and epidemiology in Africa remains largely unstudied. SINV was detected in one of the six areas, and at a single year. Detection was validated with isolation in cell culture. SINV was only detected in Cx. quinquefasciatus, adding to the list of potential vectors of SINV in nature. The SINV infection rate in mosquitoes was similar to those observed in European regions experiencing SINV outbreaks. Phylogenetic analysis placed the nearly-full genome within a cluster of Central African strains of lineage I. This cluster is thought to be at the origin of the SINV strains introduced into Europe. Our results call for studies on the prevalence of SINV infections in the region to estimate the disease burden and the interest of SINV diagnostic in case investigation.
Keywords: African Research